Pengelolaan Diversity Karyawan Dalam Organisasi - Putri, Juliana Amanda; Febriantina, Susan; Rachmadania, Rizki Firdausi (CV. ITTC INDONESIA, 2023)
This research aims to find out: Description of diversity for company X employees, Types of employee diversity in Company X, Description of the constraints in managing Diversity for company X employees, and Benefits that exist in managing employee diversity in company X. Research methods used is descriptive analysis method with a qualitative approach. The unit of analysis used in this study were 4 employees who were determined by purposive sampling technique. The data analysis technique used is an interactive model data analysis technique, starting from data reduction, data presentation, to drawing conclusions. The results of data analysis show that there is a lot of diversity (diversity) of employees at Company X and in the Management of Diversity at Company X which is still not structured enough due to the absence of Policies or Rules related to Employee Diversity Management in the long term. This research has limitations, namely only examining one variable, therefore it is suggested for further researchers to be able to examine more than one variable to strengthen and expand the research results.